2021
DOI: 10.4414/smw.2021.w30072
|View full text |Cite
|
Sign up to set email alerts
|

One year follow-up of physical performance and quality of life in patients surviving COVID-19: a prospective cohort study

Abstract: INTRODUCTION: The coronavirus disease (COVID-19) continues to affect many countries globally, with the long-term impact of the disease now being recognized. According to the latest research, some of the affected individuals continue to experience functional limitations, reduced physical performance and impaired health-related quality of life (HRQoL) even after eight months. This prospective cohort study aimed to describe the longer-term recovery of physical performance and HRQoL in COVID-19 survivors over one … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
22
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 30 publications
3
22
1
Order By: Relevance
“…Also, it is unclear if patients received rehabilitative care after hospital discharge and, if so, in what context. Other studies found no improvement in 6MWD over 12 months follow-up, which could be due to small sample sizes, 10 , 11 or between 6 and 12 months. 2 Recovery in HGS was assessed only in a cohort of patients admitted to ICU for COVID-19, indicating improved HGS over 12 months follow-up.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Also, it is unclear if patients received rehabilitative care after hospital discharge and, if so, in what context. Other studies found no improvement in 6MWD over 12 months follow-up, which could be due to small sample sizes, 10 , 11 or between 6 and 12 months. 2 Recovery in HGS was assessed only in a cohort of patients admitted to ICU for COVID-19, indicating improved HGS over 12 months follow-up.…”
Section: Discussionmentioning
confidence: 91%
“…However, these normative values have also been used in other COVID-19 studies. 2 , 3 , 10 The 650 participants in the CO-FLOW study were recruited from all patients who survived hospitalization and who visited the outpatient clinic for regular COVID-19 follow-up by pulmonary physicians in the participating hospitals. These numbers depended on the local logistics in each hospital, transfers to other regions, and temporary COVID-19 lock-down regulations, in which clinical follow-up was postponed or only performed by phone.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous study found that the incidences of anxiety and depression in the urban Chinese population were 6.0% and 5.3%, respectively [ 21 , 22 ], and the age-normalized incidences of depression and anxiety in rural Chinese adults were 5.41% and 4.94%, respectively [ 23 ]. Previous 1-year follow-up studies in recovered COVID-19 subjects found that the incidence of psychological problems (only anxiety) was as low as 10.4% [ 10 , 12 , 24 , 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…These include weakness, myalgias, sleep disturbances, shortness of breath, loss of taste and smell, headaches, physical and psychological disturbances, and cognitive impairment [4,5]. Moreover, health-related quality of life (HRQoL) has been reported to decrease in 51-62% of COVID-19 survivors after three to six months [6]. Raised titers of antibodies against SARS, Middle East respiratory syndrome coronavirus (MERS-CoV), and avian influenza A virus (H7N9) have been observed to be present for 12 months [7].…”
Section: Introductionmentioning
confidence: 99%